2017
DOI: 10.1111/psyg.12280
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for (not) discontinuing antipsychotics in dementia

Abstract: Background: The gap between high antipsychotic prescription rates for patients with dementia and the guidelines' advice to prescribe cautiously indicates that barriers to discontinuation exist. This exploratory study used the theory of planned behaviour to give a first overview of the factors that influence physicians to discontinue antipsychotics in nursing home patients with dementia. Methods: Forty-one physicians in the Netherlands completed an online survey based on the theory of planned behaviour. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Overall, the proposed models in this study explained very little of the variance in psychotropic medication use or in the use of opiates. Additional factors that should be considered in future research are beliefs of the staff, access to behavioral health providers, the use of person centered behavioral interventions, activities provided, length of stay of the resident, and timing of medication initiation (Almutairi et al, 2018; Atramont et al, 2018; Helvik et al, 2017; Janus et al, 2018; Kerns et al, 2018; MacLagan et al, 2017; Zhang, Letuchy, & Carnahan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the proposed models in this study explained very little of the variance in psychotropic medication use or in the use of opiates. Additional factors that should be considered in future research are beliefs of the staff, access to behavioral health providers, the use of person centered behavioral interventions, activities provided, length of stay of the resident, and timing of medication initiation (Almutairi et al, 2018; Atramont et al, 2018; Helvik et al, 2017; Janus et al, 2018; Kerns et al, 2018; MacLagan et al, 2017; Zhang, Letuchy, & Carnahan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A study that considered the factors regarding PD use found that nurses and general practitioners in nursing homes tended to have a low willingness to discontinue antipsychotics because of barriers such as concerns about negatively affecting residents’ quality of life and the recurrence of BPSD . Furthermore, organizational factors in nursing homes such as the number of physicians and physicians’ perceived beliefs about the positive effects of drugs for patients and care staff could influence the use of antipsychotics . In addition to these studies on antipsychotic use, the qualitative study by Smeets et al developed a conceptual framework for factors related to PD prescription in nursing homes, including physicians’ and nurses’ perceptions, knowledge of PDs and their side‐effects, decision‐making on PD use and withdrawal, and national and local policies .…”
Section: Discussionmentioning
confidence: 99%
“…In people with dementia, antidepressants are not very effective at treating depression [6], and atypical antipsychotics have a negligible effect on agitation and psychosis [7]. Non-patient related factors can also influence PTD prescriptions, such as staff-patient ratio and staff distress related to patients' symptoms [8,9], the knowledge gap among NH personnel about the related adverse effects of medication [10], communication education [11], and health care personnel's positive belief or confidence in prescribing or discontinuing medication [12,13]. Moreover, it can be challenging to monitor a drug therapy, as different screening tools for inappropriate prescribing may recommend different pharmacological measures [14].…”
Section: Introductionmentioning
confidence: 99%